2016
DOI: 10.1136/neurintsurg-2016-012581
|View full text |Cite
|
Sign up to set email alerts
|

Stent retrieval thrombectomy in acute stoke is facilitated by the concurrent use of intracranial aspiration catheters

Abstract: When using SRs for intracranial stroke thrombectomy, the concurrent use of IACs is associated with a decrease in procedural time and thrombectomy attempts compared with use of SRs alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…The first line use of contact aspiration versus stent retriever thrombectomy in LVO is evolving as a more common technique, but evidence to support its use is mixed. This technique, specifically one called “a direct aspiration as first pass technique” (ADAPT), has been studied because observational studies suggested that it might lead to earlier reperfusion and lower cost of thrombectomy 7374. This led to two randomized clinical trials, ASTER (Contact Aspiration versus Stent Retriever for Successful Revascularization) in 2017 and COMPASS (Aspiration Thrombectomy Versus Stent Retriever Thrombectomy as First-Line Approach for Large Vessel Occlusion) in 2019,757677 which both examined the ADAPT technique versus stent retriever within six hours of onset.…”
Section: Mechanical Thrombectomy For Acute Ischemic Strokementioning
confidence: 99%
“…The first line use of contact aspiration versus stent retriever thrombectomy in LVO is evolving as a more common technique, but evidence to support its use is mixed. This technique, specifically one called “a direct aspiration as first pass technique” (ADAPT), has been studied because observational studies suggested that it might lead to earlier reperfusion and lower cost of thrombectomy 7374. This led to two randomized clinical trials, ASTER (Contact Aspiration versus Stent Retriever for Successful Revascularization) in 2017 and COMPASS (Aspiration Thrombectomy Versus Stent Retriever Thrombectomy as First-Line Approach for Large Vessel Occlusion) in 2019,757677 which both examined the ADAPT technique versus stent retriever within six hours of onset.…”
Section: Mechanical Thrombectomy For Acute Ischemic Strokementioning
confidence: 99%
“…Both European and American recommendations propose that clinical trials be conducted to determine the thrombectomy device that achieves the highest rate of successful recanalization 1–4. Contact aspiration (CA) is a novel thrombectomy technique involving aspiration of the thrombus through a large-bore catheter 5–18. The CA technique employs large-bore aspiration catheters that have the advantage of being easily tracked for introduction into the cerebral circulation and removal of the thrombus via negative pressure aspiration.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding procedures, the rate of combined procedure using a stent retriever with aspiration catheter was approximately 70% in the favorable and unfavorable outcome groups. Several studies have reported the advantages of combined procedures, [14][15][16] but we have performed the procedure, emphasizing that a higher recanalization rate was achieved on the first pass than the procedures with a stent retriever or aspiration catheter alone. 17) In this study, combined procedures comprised the greater portion.…”
Section: The Evt Groupmentioning
confidence: 99%